Mainan Edukasi untuk Kegiatan Edukasi Hemat Energi “Earth Hour Bandung” - Afif Muhammad Fadhil Utomo; Sulistyo Setiawan (Aliansi Desainer Produk Industri Indonesia (ADPII), 2022)
This research is the process of designing an educational toy product regarding environmentally friendly alternative energy for the SIMARGI (Education Saving Energy) community